Teacher communication : a guide to relational, organizational, and classroom communication - White, Ken W., 1950- (Rowman and Littlefield, 2016)
For pre- and in-service teachers, Teacher Communication is a one-of-a-kind resource for teacher education courses and workshops that want teachers to develop effective relational, organization and classroom communication skills. Its author focuses on the interpersonal, dialogical and relational aspects of teaching and learning, offering useful attitudes and strategies to enrich instructional skills. Readers learn how to keep a classroom interpersonal, how to communicate effectively with students, parents and colleagues, how to facilitate groups and discussions, how to address conflict and how.- Resumé vydavatel
Keywords: pedagogická komunikace; učitel a žák; communication in learning and scholarship; teacher and learner; elektronické knihy; příručky; electronic books; handbooks and manuals